2018
DOI: 10.1038/s41467-018-07287-7
|View full text |Cite|
|
Sign up to set email alerts
|

Serotonin signals through a gut-liver axis to regulate hepatic steatosis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is increasing in worldwide prevalence, closely tracking the obesity epidemic, but specific pharmaceutical treatments for NAFLD are lacking. Defining the key molecular pathways underlying the pathogenesis of NAFLD is essential for developing new drugs. Here we demonstrate that inhibition of gut-derived serotonin synthesis ameliorates hepatic steatosis through a reduction in liver serotonin receptor 2A (HTR2A) signaling. Local serotonin concentrations in the portal blood,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 46 publications
8
122
0
2
Order By: Relevance
“…High fat fed mice have increased levels of 5-HT in serum 76 and in BAT, 54 and inhibition of peripheral 5-HT synthesis reduces their adiposity, metabolic dysfunction, 54,77 and hepatic steatosis. 78 This effect was at least partially attributed to increased β3-adrenergic induction of UCP1mediated, BAT thermogenesis. 54 BAT SNA is impaired in rats maintained chronically on a high fat diet, 79,80 similar to the reduction in BAT thermogenesis in obese humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fat fed mice have increased levels of 5-HT in serum 76 and in BAT, 54 and inhibition of peripheral 5-HT synthesis reduces their adiposity, metabolic dysfunction, 54,77 and hepatic steatosis. 78 This effect was at least partially attributed to increased β3-adrenergic induction of UCP1mediated, BAT thermogenesis. 54 BAT SNA is impaired in rats maintained chronically on a high fat diet, 79,80 similar to the reduction in BAT thermogenesis in obese humans.…”
Section: Discussionmentioning
confidence: 99%
“…High fat fed mice have increased levels of 5‐HT in serum and in BAT, and inhibition of peripheral 5‐HT synthesis reduces their adiposity, metabolic dysfunction, and hepatic steatosis . This effect was at least partially attributed to increased β3‐adrenergic induction of UCP1‐mediated, BAT thermogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [65] demonstrated that the portal blood serotonin concentrations are selectively increased by high-fat diet feeding in mice, and they have endocrine effects on the liver. In fact, nutrient infusion induces 5-HT production in the human gut while the liver is the first organ to encounter gut-derived serotonin via the portal vein.…”
Section: Gut-microbiota and Serotonin Metabolismmentioning
confidence: 99%
“…У роботі J. Namkung et al за допомогою генетичних і фармакологічних моделей інгібування серотоніну у мишей досліджувались функціональні зв'язки між стеатозом печінки і гормоном. Було показано, що серотонін має прямий вплив на накопичення ліпідів в печінці, а пригнічення його синтезу в кишечнику полегшує прояви стеатозу печінки [28,29]. Однак, досліджень в цьому напрямку у людей ще [30].…”
Section: серотонінunclassified
“…Отже, збільшення рівня гормону в ЦНС сприяє зменшенню споживання їжі і маси тіла, а гіперпродукція серотоніну в кишечнику, як вважають, призводить до ожиріння [27]. У дослідженнях на мишах концентра ція серотоніну в портальній вені підвищувалася при харчуванні продуктами з високим вмістом жиру [28]. У роботі A. Ojeda-Rodríguez et.…”
Section: серотонінunclassified